Lack of genetic association of the three more common polymorphisms of CARD15 with psoriatic arthritis and psoriasis in a German cohort. Issue 6 (11th November 2004) - Lascorz, J; Burkhardt, H; Hüffmeier, U; Böhm, B; Schürmeyer-Horst, F; Lohmann, J; Ständer, M; Wendler, J; Kelsch, R; Baumann, C; Küster, W; Traupe, H; et al.
Abstract : Objective: To determine whether the three common independent sequence variants of the putative pleiotropic non-MHC autoimmune gene CARD15 influence disease susceptibility in large German cohorts of patients with psoriatic arthritis and psoriasis vulgaris, before and after stratification to HLA-C. Methods: DNA was obtained from 375 patients with psoriatic arthritis, 281 patients with psoriasis vulgaris without joint involvement, and 376 controls. The three variants of the CARD15 gene (R702W, G908R, leu1007fsinsC), and two single nucleotide polymorphisms of the HCR gene (HCR-325, HCR-2327) for HLA-C stratification were genotyped using allelic discrimination Taqman assays. Results: No significant differences in genotype frequencies were observed between controls and either the psoriatic arthritis or the psoriasis vulgaris patient population, even after stratification to HLA-C in both patient cohorts, or to the type of joint involvement within the psoriatic arthritis group. Conclusions: The lack of genetic association between the most common Crohn's disease alleles of the CARD15 gene and psoriatic joint disease on large cohorts of white patients does not support a recently claimed role for CARD15 as the first non-MHC susceptibility gene in the pathogenesis of psoriatic arthritis, but confirms and extends previous studies in the case of psoriasis vulgaris.